Contribution of ICT Literacy and Teachers Work Ethic on the Quality of Distance Education in State Junior High Schools of Sukoharjo Sub-District - Darus Rohman; Sutama Sutama; Darsinah Darsinah (Budapest International Research and Critics University, 2021)
The aim of this study is to investigate the effect of ICT literacy and teacher work ethic on the quality of distance education in Sukoharjo Sub-District state senior high schools. The sample included 200 teachers from state junior high schools in Sukoharjo Sub-District. A questionnaire is used to collect data. Multiple linear regression analysis was used to analyze the data in this study. Previously, validity tests, reliability tests, and classical assumption tests were used to analyze data. The findings indicated that: 1) Information and communication tachnology literacy contributed considerably to the quality of remote education. This is evident from the T test result of 4,401, p of 0.000 0.05. 2) The work ethos of teachers has a substantial beneficial effect on the quality of distance education. This is established using the T test of 3,486, with a p value of 0.0010.05. Advice based on the findings of this study may be utilized as a guideline for teachers' ICT skills training, as well as a critical foundation for the methodical construction, enhancement, and sustainability of distance education.